2019
DOI: 10.1111/jre.12691
|View full text |Cite
|
Sign up to set email alerts
|

Role of Porphyromonas gingivalis in oral squamous cell carcinoma development: A systematic review

Abstract: Objective The target of the current systematic review is to gather and synthesize the most recent scientific information about the role of Porphyromonas gingivalis in the molecular pathways of oral squamous cell carcinoma (OSCC). Background Oral squamous cell carcinoma is the most common malignancy of the oral cavity, with a poor prognosis and a low survival rate. Etiology is multifactorial but consumption of tobacco and alcohol is the most important risk factors. P gingivalis is a Gram‐negative anaerobic bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 45 publications
0
47
0
Order By: Relevance
“…Utilizing a murine model of periodontitis-associated oral tumorigenesis, Binder Gallimidi et al showed that chronic bacterial co-infection of P. gingivalis and F. nucleatum promotes OSCC via direct interaction with oral epithelial cells through Toll-like receptors, with an increase in expression of TLR2 in OSCC cells and IL-6 in both cells and the mouse model (160). A detailed review of all the studies where P. gingivalis has been associated with the development of OSCC has been recently published by Lafuente Ibañez de Mendoza et al (161).…”
Section: The Microbiome and Oral Cancermentioning
confidence: 99%
“…Utilizing a murine model of periodontitis-associated oral tumorigenesis, Binder Gallimidi et al showed that chronic bacterial co-infection of P. gingivalis and F. nucleatum promotes OSCC via direct interaction with oral epithelial cells through Toll-like receptors, with an increase in expression of TLR2 in OSCC cells and IL-6 in both cells and the mouse model (160). A detailed review of all the studies where P. gingivalis has been associated with the development of OSCC has been recently published by Lafuente Ibañez de Mendoza et al (161).…”
Section: The Microbiome and Oral Cancermentioning
confidence: 99%
“…Interestingly, a mixed infection of F. nucleatum and Porphyromonas gingivalis (P. gingivalis) has been shown to be much more effective than mono-infection in experimental periodontitis (Polak et al, 2009). In addition, P. gingivalis, a major pathogen of periodontitis, is also associated with OSCC (Geng et al, 2017;Lafuente Ibanez de Mendoza et al, 2020;Wen et al, 2020), esophageal squamous cell carcinoma (Gao et al, 2016), pancreatic cancer (Michaud et al, 2013), cardiovascular disease (Gibson et al, 2004) and rheumatoid arthritis (Wegner et al, 2010). In the mucosa-adherent and fecal microbiota, Porphyromonas has been shown to be enriched in CRC patients (Chen et al, 2012;Ahn et al, 2013;Wu et al, 2013;Zackular et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The possible mechanisms include epithelial mesenchymal transformation in malignant cells, tumor proliferation, and tumor invasion. However, the accuracy of this finding is still waiting to be confirmed in in vitro studies and animal models (Hoppe et al, 2016;Lafuente Ibanez de Mendoza et al, 2019).…”
Section: Metabolismmentioning
confidence: 99%
“…Promote the overexpression of nuclear factor kappa-light-chain-enhancer of activated B cells and the activation of cyclin-D1, an epidermal growth factor receptor ligand that promote the growth of tumors, eventually provoking nuclear translocation; epithelial mesenchymal transformation in malignant cells, tumor proliferation and tumor invasion (Hoppe et al, 2016;Lafuente Ibanez de Mendoza et al, 2019).…”
Section: Osccmentioning
confidence: 99%